1995
DOI: 10.1007/bf00311695
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thymectomy on myasthenia gravis, thrombocytopenia, and granulocytopenia associated with thymoma: Report of a case

Abstract: We report the case of a 47-year-old woman with thymoma who developed myasthenia gravis, thrombocytopenia, and granulocytopenia, simultaneously, the concurrent association of these four disorders being extremely rare. Thymectomy was performed, and, during the post-thymectomy course, there were surprising findings concerning the recovery of not only the myasthenia gravis but also of the hematologic disorders. Immediately after thymectomy, the myasthenic symptoms completely disappeared, and the granulocyte and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It has been reported the case of a patient with thymoma and granulocytopenia in whom a decrease in anti-pANCA antibody titer and elevation of granulocytes in peripheral blood was observed after thymectomy. 9 However, in other cases neutropenia has not resolved after thymectomy and a second line of treatment is necessary. 10,11 The medical treatment of these patients is not established currently due to low incidence of cases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported the case of a patient with thymoma and granulocytopenia in whom a decrease in anti-pANCA antibody titer and elevation of granulocytes in peripheral blood was observed after thymectomy. 9 However, in other cases neutropenia has not resolved after thymectomy and a second line of treatment is necessary. 10,11 The medical treatment of these patients is not established currently due to low incidence of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Response to immunosuppressive therapy is often used to confirm the diagnosis in dogs, while documentation of antineutrophil antibodies is preferred to confirm the diagnosis in human medicine. Antineutrophil antibodies were documented in human patients with thymoma and granulocytopenia,20 21 although this is an inconsistent finding,11 possibly due to specific toxicity to the myelomonocytic precursor cells in the bone marrow. Antineutrophil antibodies have been documented in dogs with immune‐mediated neutropenia,22 23 and they could not be used to distinguish primary from secondary disease.…”
Section: Discussionmentioning
confidence: 99%
“…PRCA is also known as a concomitant disorder with MG. Th ey concluded that thymoma, bulbar involvement and high level of AChR antibodies were signifi cantly higher in patients with PRCA. Kobayashi et al report a case of a patient with MG, thymoma, thrombocytopenia and granulocytopenia 6 . After thymectomy, not only the symptoms of MG but also hematologic fi ndings improved.…”
Section: Discussionmentioning
confidence: 99%